Cerrahpasa Faculty of Medicine’s Steps of Foundation - Altıntaş, Ayten (Cerrahpaşa Medical Journal, 2014)
Cerrahpasa Faculty of Medicine is a part of modern medical education and it goes on continuously in years. After Istanbul Faculty of Medicine separated into two, Cerrahpasa faculty of medicine was founded in 1967. Medical Ecucation in Turkey was begin in 1827 and after that day it goes on by improving and innovating.from 1933 it’s named Istanbul Faculty of Medicine and after 1967 it developed itself clinic, building and staff. Cerrahpasa Faculty of Medicine identified with Cerrahpasa Hospital. Cerrahpasa Hospital founded in 1893 and from 1933 work constantly as being Istanbul’ Faculty of Medicine’s Clinics. The idea of founding second faculty of medicine in Istanbul University was come up in 1961 and determine by the help of government planning organization and demands of government .Istanbul Faculty of Medicine was working both in Cerrahpasa and Capa campuses from 1964 but in 2 April 1967 professor’s committee decided to found Cerrahpasa Faculty. Than on 27 .07.1967 Istanbul University senator affirm the decision. 28.07.1967 In Ministry of Education accept and Faculty has started to work with 903 student in 2.10.1967.